New Standards for Teaching Middle School Science: Now That We Have Them, What Do We Do? - Randal Harrington (Journal of Research in Rural Education, 1997)
Middle school science teachers are currently facing a plethora ofdocuments describing what and how science should be taught. In some cases, the new standards represent a fresh confirmation for some teachers of what they have been doing for a long time. For others, they represent a significant departure from current curricula and will require fundamental changes in attitudes regarding what and how teachers teach and how students learn. In almost all cases, the successful transition to a student-centered active-engagement classroom will require teachers to have detailed knowledge about how their students think and the specific difficulties they encounter as they struggle to understand basic concepts. To obtain this detailed knowledge, a research group called the Laboratory for Research in Physics Education has been formed at the University ofMaine. This group examines specific sections ofthe new science standards, developing new curricula based on the results of physics education research, collaborating with rural middle school teachers on the implementation ofthat curricula, and performing research in rural classrooms to assess the effectiveness ofthe materials and the methods. This paper will describe one such project on kinematics piloted at a rural middle school in Spring of 1996. This project is a modelfor how university faculty, graduate students, and K-12 teachers can work together toward the common goal ofimproving the teaching and learning ofscience.